Influence of Crack Spacing/Layer Thickness Value on Reflection Crack Propagation Mechanism Under Low Temperatures - Bao, Chunyan; Liu, Qi; Xia, Yingjie; Cui, Yi; Cao, Zongyong; Qian, Yidong; Liu, Minghao; Mu, Chaoqian; Wang, Hongliang (Frontiers in Earth Science, 2022)
The damage of asphalt concrete pavement (AC pavement) structure caused by reflection crack is an urgent problem in many areas of China, especially in cold regions of China, so it is necessary to study how to reduce the reflective cracking and prevent the AC pavement structures cracking. The acoustic emission (AE) information is fetched in this paper to study the AE characteristics of pavement structures and the crack propagation law inside the system. On the above basis, cracks with crack spacing/layer thickness values of 1.25, 2.5, 3.75, and 5 were prefabricated in the foundation course by the numerical simulation method. The models with different foundation course crack spacing were calculated by Realistic Failure Process Analysis finite element software. The influence of varying crack spacing on the propagation mechanism of reflective cracks in the foundation course structure was studied. The results show that the AC pavement structure has prominent AE characteristics. The faster the cooling rate is, the more serious the damage to the AC pavement surface is. In addition, with the increase of crack spacing/layer thickness value, the stress level between cracks increases continuously. Most of the stress will make the cracks expand toward the foundation course structure, and only a tiny part of stress is used to form reflective cracks. In practical engineering, it is suggested to increase the crack resistance of foundation course materials and preset some small spacing cracks in the large spacing cracks in the foundation course.